Madeira and sugar protectionism (1895-1918) - Câmara, Benedita (1998)
The purpose of this article is to determine the reason why sugar protectionism called for the permanent exercise of the arbitral function of the Central Market for Agricultural Produce, although its operational structure was similar to that of the cereal protectionism begun in 1889, which did not need this function. For the examination of this question we tried to find out what the nature of the relationship between the diverse Madeira industrial sectors related with the transformation of the raw material in question - grape spirit producers, on the one hand, and sugar and alcohol producers, on the other. Particular importance was placed on the type of relationship that interlaced these with the sugar cane and wine producers. Sugar cane spirit was an alternative to common wine in terms of public consumption. Spirit distilled from sugar substituted grape spirit in the production of the Madeira fortified wines. This explains the instability of the relations between the wine-makers and the alcohol producers. Despite the fact that the international sugar prices were particularly low, this system contributed to the stimulation of the export of sugar from the island to the continental market. With this in mind we have attempted to explain how it was possible that this evolution was compatible with the nature of the Portuguese taxation system and with the aspirations of the sugar industry in the Portuguese colonies in Africa. Finally, we analysed the re-formulations introduced under this system and put these in relation with the commitment that the regional powers, both private and public, gave to sugar protectionism as a driving force the island's economy.